Unlucky to Be Young? The Long-Term Effects of School Starting Age on Smoking Behaviour and Health - Michael Bahrs; Mathias Schumann (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2016)
In this study, we analyse the long-term effects of school starting age on smoking behaviour and health in adulthood. School entry rules combined with birth month are used as an instrument for school starting age. The analysis adopts the German Socio- Economic Panel data and employs a fuzzy regression discontinuity design. The results reveal that school starting age reduces the long-term risk to smoke, improves long-term health, and affects physical rather than mental health. In addition, we find that the relative age composition of peers and the school environment are important mechanisms.
Keywords: I12; I21; I28; 330; smoking; health; peer effects; education; school starting age; regression discontinuity design